A study on the effectiveness of conveying information through Melaka Hari Ini newspaper in Melaka / Rozeta Mohd Hanafiah - Mohd Hanafiah, Rozeta (Faculty of Business and Management, 2005)
Melaka Hari lni is a newspaper published by the state government of Melaka since 1982. However, people's awareness towards this newspaper is still very low. Thus, few questions arise need to be answers. The focus of this study is to determine whether Melaka Hari ini is effectively channeling the information from the ruling party to the public. The data was collected through surveys as there was no secondary data being obtained. After the conclusion has been made, few recommendations were brought up with hope to improve the newspaper in the future.